(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
This article presents developments from an arts-based research project that investigates the application of A/r/tographic methodology in technical fashion education, articulating art, research, and teaching through a pedagogical proposition developed with students from the Technical Course in Fashion Styling and Coordination at Senac Pindamonhangaba. The study aimed to analyze how A/r/tography, in dialogue with cartography and the notion of rhizome, may foster more sensitive, collaborative, and reflective educational practices. The investigation, qualitative in nature, derives from a broader study with a qualitative and quantitative approach and, in the scope presented here, focuses on an action-research experience carried out in three 3.5-hour meetings, held on June 14, 17, and 18, 2024, with the participation of 15 students, the teacher-researcher, and a professional responsible for visual documentation. The instruments used for producing information included participant observation, field diary, photographic and audiovisual records, rhizomatic maps, continuous line drawings, experiments with natural fibers, embroidery, patternmaking, and exhibition installation. The analysis considered the connections produced among the field trip to Greece, visual repertoires, mythology, textile practices, collective creation, and the construction of the garment-artwork Luminosa Selene. The results indicate that the experience fostered shifts in the understanding of the creative process, expanded students’ participation in the symbolic construction of the piece, and repositioned the teacher as artist, researcher, and educator. Thus, the article contributes to debates on Arts-based Educational Research, A/r/tography, and technical fashion education, highlighting embroidery and thread as material, narrative, and methodological operators of learning.